Afterword: On the Study of Religion in Public Institutions - Cadge, Wendy (Journal for the scientific study of religion, 2017)
Each of the essays presented enters the conversation about religion in public institutions through a different analytic doorway. The essays presented here enlarge and challenge various aspects of our initial analytic framework and enable us to see our blind spots and propose next steps. Reflecting on the contributions, we outline three additional issues to consider: the centrality of religion to the organizational identity or to organizational goal achievement, the effect of a specific aspect of the institution's organizational structure on religion, and the relevance of larger cross-national differences for explaining differences in the same institution across national borders. Finally, we call for additional cross-national case studies that will enable continued development of the comparative framework we propose.